By Lagrange’s method the auxiliary equations of the given differential equation are as following:
"\\frac{\ud835\udc51\ud835\udc65}{\ud835\udc65\u2212\ud835\udc66}=\\frac{\ud835\udc51\ud835\udc66}{\ud835\udc66\u2212\ud835\udc65\u2212\ud835\udc67}=\\frac{\ud835\udc51\ud835\udc67}{\ud835\udc67}"
"\\implies \\frac{\ud835\udc51\ud835\udc65}{\ud835\udc65\u2212\ud835\udc66}=\\frac{\ud835\udc51\ud835\udc66}{\ud835\udc66\u2212\ud835\udc65\u2212\ud835\udc67}=\\frac{\ud835\udc51\ud835\udc67}{\ud835\udc67} = \\frac{dx+dy+dz}{0} \\\\\n\\implies dx+dy+dz =0 \\implies x+y+z = c_1"
Hence from the first fraction, we have "\\frac{\ud835\udc51\ud835\udc65}{\ud835\udc65\u2212\ud835\udc66}=\\frac{\ud835\udc51\ud835\udc66}{\ud835\udc66\u2212\ud835\udc65\u2212\ud835\udc67}"
"\\implies \\frac{\ud835\udc51\ud835\udc66}{\ud835\udc66\u2212c_1+y}=\\frac{\ud835\udc51z}{z}"
Now, by integrating on both sides we get "(1\/2)\\log(2y-c_1) =\\log(z)+\\log(\\sqrt{c_2})\n\\implies c_2 = \\frac{y-x-z}{z^2}" .
Since "x+y+z=c_1" and "\\frac{y-x-z}{z^2}=c_2" are independent solutions of the given differential equation, so a solution of the given differential equation is
"c_2= f(c_1) \\implies \\frac{y-x-z}{z^2} = f(x+y+z)" ________(1)
On "x^2+y^2 = 1, z=1" , so put "x= \\cos{(t)}, y = \\sin{(t)}" and put in solution, we get
"\\sin{(t)}-\\cos{(t)}=f(\\cos{(t)}+\\sin{(t)})" ________(2)
So, the solution of the given differential equation is given by (1), where the function is given by (2).
Comments
Leave a comment